An Integrated Approach Based on Network Analysis Combined With Experimental Verification Reveals PI3K/Akt/Nrf2 Signaling Is an Important Way for the Anti-Myocardial Ischemia Activity of Yi-Qi-Tong-Luo Capsule - Duan, Huxinyue; Li, Meiyan; Liu, Jia; Sun, Jiayi; Wu, Chunjie; Chen, Yu; Guo, Xiaohui; Liu, Xinglong (Frontiers in Pharmacology, 2022)
Yiqi-Tongluo Capsule (YTC) is a Chinese traditional patent medicine that has been used in the treatment of myocardial ischemia (MI). However, its molecular mechanisms against MI have not been clear. In this study, we used bioinformatics analysis and experimental verification to explore the potential active components and molecular mechanisms of YTC for the treatment of MI. Firstly, the main components in the capsules and the potential targets of these components were predicted by online databases. Similarly, the MI related genes were collected from Genecards and OMIM databases. The drug targets and disease targets were intersected, and 87 overlapping targets were obtained as potential targets. The protein-protein interaction (PPI) and Drug-Molecular-Target-Disease Network (DMTD) were constructed, and GO enrichment analysis and KEGG pathway enrichment analysis were performed. Bioinformatics analysis suggested that oxidative stress is an important biological process, and PI3K/Akt and apoptosis are the core pathways, indicating that the pharmacological mechanism of YTC against MI might be related to antioxidant stress and inhibition of apoptosis. Based on the H2O2-stimulated H9c2 cells model, flow cytometry, western blot and immunofluorescence experiments were performed to verify the network pharmacological prediction. The results showed that YTC might alleviate MI by suppressing apoptosis induced by oxidative stress via the PI3K/Akt / Nrf2 signal pathway.